Characterizing SARS-CoV-2 Transcription of Subgenomic and Genomic RNAs During Early Human Infection Using Multiplexed Droplet Digital Polymerase Chain Reaction. (5th December 2022) - Hwang, Hyon S; Lo, Che-Min; Murphy, Michael; Grudda, Tanner; Gallagher, Nicholas; Luo, Chun Huai; Robinson, Matthew L; Mirza, Agha; Conte, Madison; Conte, Abigail; Zhou, Ruifeng; Vergara, Candelaria; et al.
Abstract: Background: Control of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission requires understanding SARS-CoV-2 replication dynamics. Methods: We developed a multiplexed droplet digital polymerase chain reaction (ddPCR) assay to quantify SARS-CoV-2 subgenomic RNAs (sgRNAs), which are only produced during active viral replication, and discriminate them from genomic RNAs (gRNAs). We applied the assay to specimens from 144 people with single nasopharyngeal samples and 27 people with >1 sample. Results were compared to quantitative PCR (qPCR) and viral culture. Results: sgRNAs were quantifiable across a range of qPCR cycle threshold (Ct) values and correlated with Ct values. The ratio sgRNA:gRNA was stable across a wide range of Ct values, whereas adjusted amounts of N sgRNA to a human housekeeping gene declined with higher Ct values. Adjusted sgRNA and gRNA amounts were quantifiable in culture-negative samples, although levels were significantly lower than in culture-positive samples. Daily testing of 6 persons revealed that sgRNA is concordant with culture results during the first week of infection but may be discordant with culture later in infection. sgRNA:gRNA is constant during infection despite changes in viral culture. Conclusions: Ct values from qPCR correlate with active viral replication. More work is needed to understand why some cultures are negative despite presence of sgRNA. Abstract : We developed a multiplex droplet digital PCR assay to simultaneously quantify subgenomic and genomic viral RNAs during human SARS-CoV-2 infection. Kinetics of subgenomic RNAs during acute SARS-CoV-2 infection corresponded with viral culture positivity and abundance of total SARS-CoV-2 RNA.